HISTOCHEMICAL STUDY OF MUCOPOLYSSACHARIDES IN STOMACH OF BUFFALO(BUBALUS-BUBALIS) - Fawzi S.Al-Asadi; Sawsan Gafoori Ahmed (Basrah Journal of Veterinary Research)
Ten samples of baffula stomach including rumen, reticulum, omasum Abomasum were collected from slaughter of Basrah .Tissue sections were done and stained with alcian blue and acridin orange dyes then photographed by light and fluorescent microscope .The histochemical study showed that all four parts of stomach consist of mucosa,submucosa ,muscular and serosal layer .The histochemical study showed that mucopolysacchrides distributed in all histological layers but with high density in the mucosal layer.